THE INVESTIGATION OF JUNIOR HIGH SCHOOL TEACHERS' CHALLENGES IN DEVELOPING TEACHING MATERIALS - Ivani Noviarani, - (2018)
The present study entitled "The Investigation of Junior High School Teachers' Challenges in Developing Teaching Materials" aimed at knowing how junior high school teachers develop teaching materials as well as investigating the challenges. The study employed qualitative case study design. The data collected through documents analysis and interviews are analyzed qualitatively based on interactive model proposed by Miles and Huberman (1994). The findings indicate that the procedure used by the teachers in developing teaching materials is as follows: identifying needs or problems, exploring needs or problems, realizing contextual contents, pedagogical realization, and composing teaching materials based on stipulated lesson plan. Meanwhile, the challenges encountered in developing teaching materials are the lack of conformity between the 2013 curriculum approach and the language learning material, the difficulty in adjusting teaching approach syntax and teaching models syntax, the instability of the students' condition in the classroom, the lack understanding on learning methods, the unavailable teaching media tools and equipment needed, and the lack of time in preparing the assessment. Based on the findings, it can be concluded various procedures of teaching materials development proposed by the experts can be used. Moreover, it is necessary for teachers to overcome the challenges based on experts' theories.;---Penelitian dengan judul "The Investigation of Junior High School Teachers' Challenges in Developing Teaching Materials" ini ditujukan untuk mengetahui bagaimana guru sekolah menengah pertama mengembangkan bahan ajar dana pa sajakah tantangannya. Penelitian ini menerapkan metode kualitatif studi kasus. Data dikumpulkan melalui analisis dokumen dan wawancara yang dianalisis secara kualitatif berdasarkan model interaktif dari Miles dan Huberman (1994). Temuan dalam penelitian ini menunjukkan langkah-langkah pengembangan bahan ajar yang dilakukan oleh guru, yaitu: mengidentifikasi kebutuhan-kebutuhan atau masalah-masalah, mengeksplorasi kebutuhan-kebutuhan atau masalah-masalah, meralisasikan konten yang kontekstual, merealisasikan elemen-elemen pedagogis, dan menyusun bahan ajar berdasarkan rencana pembelajaran yang telah disusun. Selain itu, tantangan yang dihadapi oleh guru dalam mengembangkan bahan ajar adalah kurang sesuainya pendekatan kurikulum 2013 dan materi pembelajaran bahasa, kesulitan dalam menyesuaikan sintaksis pendekatan pembelajaran dan sintaksis model pembelajaran, tidak stabilnya kondisi siswa di kelas, kurangnya pemahaman tentang metode pembelajaran, alat-alat media pembelajaran yang tidak tersedia, dan kurangnya waktu untuk mempersiapkan penilaian. Berdasarkan temuan tersebut, dapat disimpulkan bahwa berbagai prosedur pengembangan bahan ajar yang dikemukakan oleh para ahli diterapkan dengan baik. Selain itu, perlu bagi guru untuk mengatasi tantangan dalam mengembangkan bahan ajar dengan dasar teori dari para ahli.